2008
DOI: 10.3324/haematol.12871
|View full text |Cite
|
Sign up to set email alerts
|

Long-term responses and outcomes following immunosuppressive therapy in large granular lymphocyte leukemia-associated pure red cell aplasia: a Nationwide Cohort Study in Japan for the PRCA Collaborative Study Group

Abstract: Large granular lymphocyte leukemia-associated pure red cell aplasia accounts for a significant portion of secondary pure red cell aplasia cases. However, because of its rarity, long-term responses and relapse rates after immunosuppressive therapy are largely unknown. We conducted a nationwide survey in Japan and collected 185 evaluable patients. Fourteen patients with large granular lymphocyte leukemia-associated pure red cell aplasia were evaluated. Cyclophosphamide, cyclosporine A and prednisolone produced r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 19 publications
2
59
0
1
Order By: Relevance
“…The cyclophosphamide response rate compares favorably with that of MTX, with an ORR of 66% and 55%, respectively, in the French series. 13,59,65,71,72 Time to response ranges from one to 4 months in our experience. Importantly, we have reported that 11 of 15 patients responded to cyclophosphamide after having failed to respond to MTX.…”
Section: Cyclophosphamidementioning
confidence: 99%
See 1 more Smart Citation
“…The cyclophosphamide response rate compares favorably with that of MTX, with an ORR of 66% and 55%, respectively, in the French series. 13,59,65,71,72 Time to response ranges from one to 4 months in our experience. Importantly, we have reported that 11 of 15 patients responded to cyclophosphamide after having failed to respond to MTX.…”
Section: Cyclophosphamidementioning
confidence: 99%
“…12,13,[65][66][67]69,[72][73][74][75] Response rates vary from one study to another and are usually better in the small series. Patients with pure red cell aplasia appear to have a good response.…”
Section: Cyclosporinementioning
confidence: 99%
“…The cytopenias are usually corrected without the clone being eradicated, since this is often resistant to treatment. Immunomodulatory drugs, such as methotrexate (10 mg/m 2 /week), cyclosporine A (5-10 mg/kg/day) or low dose cyclophosphamide (50 to 100 mg/day) [37][38][39][40] are commonly used. Corticosteroids may be useful as a part of the initial treatment to accelerate response and growth factors are often used.…”
mentioning
confidence: 99%
“…In this symposium, based on a nationwide survey in Japan, current strategies for the treatment of PRCA were introduced in a presidential lecture. Although this issue is not reviewed in this PIH series, relevant articles can be found elsewhere [21,22] as can focused articles on idiopathic [23], thymoma-associated [24], large granular lymphocyte leukemia-associated [25] and lymphoma-associated PRCA [26]. Oligodeoxynucleotides (ODN) are another deserving wonder that does not appear in this PIH series.…”
Section: Heme and Ironmentioning
confidence: 99%